A Role for in Vitro Disease Models in the Landscape of Preclinical Cardiotoxicity and Safety Testing - Varma Vijayalakshmi (Journal of Evolving Stem Cell Research, 2017)
Drug-induced cardiotoxicity is one of the predominant reasons for drug attrition and withdrawals. This is of critical concern when potentially cardiotoxic drugs are administered to individuals with inherited arrhythmogenic cardiac diseases or with metabolic diseases such as obesity and diabetes, which are key risk factors for cardiovascular diseases. Pathophysiological alteration prevalent under such conditions can alter or exacerbate cardiotoxic responses. The growing incidence of obesity, diabetes and metabolic syndrome subject a significant percentage of the population to drug treatments, thereby augmenting their risk for drug-induced cardiovascular toxicity. Hence, screening for drug-induced cardiotoxicity early in the preclinical stages of drug development, by using appropriate human disease models, can be effective in ensuring safety in clinical trials and preventing late stage and post-marketing drug withdrawals owing to cardiotoxicity. The advent of human pluripotent stem cells (hPSC) and induced pluripotent stem cell (iPSC)-derived cardiomyocytes are revolutionizing safety/toxicity screening in human cells by providing relevant human-specific, renewable model systems to explore human drug toxicity. The ability to generate patient-specific iPSCs that can model cardiac diseases, now offers a valuable option that can further improve drug safety assessments and enable a more accurate prediction of toxicity that occurs in the representative population that are prescribed the drugs. Use of appropriate disease models will not only provide cost savings by decreasing potential drug attrition and withdrawals, seen with many drugs, but will also be a promising option to advance precision medicine
Keywords: Preclinical cardiotoxicity